PRINCIPLES OF TREATMENT OF ANEMIA WITH CHRONIC HEART FAILURE - Gadaev, A.G.; Turaqulov, R.I.; Kurbonov, A.K.; Tosheva, Kh.B.; Erkinova, N.A.; Xalilova, F.A.; Djuraeva, N.D. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The effectiveness of the treatment of patients with chronic heart failure also depends on the elimination of associated conditions that can lead to the progression and complication of the disease. Treatment of anemia, first of all, should be based on its etiological factor. The review presents data on the current approach to the treatment of anemia in patients with chronic heart failure.